Explaining threshold effects of globalization on poverty: An institutional perspective - Alice Sindzingre (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The paper focuses on the non-linearity of the transmission of the impact of globalization on poverty and the existence of threshold effects. Institutions constitute a critical factor for the creation of threshold effects in the impact of globalization on poverty. Institutions—their credibility, ability to be transformed by globalization, and the ways they give the poor access to the beneficial effects of globalization—determine whether the benefits of globalization are spread to the poor or are locked in by particular groups. They also determine whether or not the negative shocks associated with globalization are transmitted in an unfettered manner. The paper presents a theory of institutions that distinguishes several components, which evolve differently and explain the threshold effects that institutions generate upon the impact of globalization on the poor. The paper then shows that social institutions and norms have a critical role in the generation of these threshold effects. It finally examines the interactions between social institutions and state policies institutions, which may contribute to the formation of poverty traps. – institutions ; poverty ; globalization ; social norms
Keywords: B52; P48; Z13; 330; Armut; Globalisierung; Soziale Norm